Maps of Canberra by suburbs. Waramanga - Australia. Department of the Capital Territory (Canberra : Australian Government Publishing Service, 1984)
Map showing land tenure and land usage.
Index to suburbs and villages.
Keywords: Land tenure -- Australian Capital Territory -- Waramanga -- Maps; Waramanga (A.C.T.) -- Maps